Magnetic Resonance-Guided Laser Induced Thermal Therapy for Glioblastoma Multiforme: A Review - Norred, Sarah E. (Hindawi Publishing Corporation, 2014)
Magnetic resonance-guided laser induced thermotherapy (MRgLITT) has become an increasingly relevant therapy for tumor ablation due to its minimally invasive approach and broad applicability across many tissue types. The current state of the art applies laser irradiation via cooled optical fiber applicators in order to generate ablative heat and necrosis in tumor tissue. Magnetic resonance temperature imaging (MRTI) is used concurrently with this therapy to plan treatments and visualize tumor necrosis. Though application in neurosurgery remains in its infancy, MRgLITT has been found to be a promising therapy for many types of brain tumors. This review examines the current use of MRgLITT with regard to the special clinical challenge of glioblastoma multiforme and examines the potential applications of next-generation nanotherapy specific to the treatment of glioblastoma.